Status Gizi dan Perkembangan Motorik Balita Usia 24-59 Bulan di Wilayah Pertanian: Status Gizi dan Perkembangan Motorik Balita Usia 24-59 Bulan di Wilayah Pertanian Kabupaten Semarang - Ihza, Shalza Ellian Farthur; Pangestuti, Dina Rahayuning; Asna, Alfi Fairuz; Lisnawati, Naintina (Amerta Nutrition, 2024)
Background: Poor nutritional status during the growth and development of toddlers is irreversible. It can affect the inadequate functioning of various body systems, including the nervous and muscular systems that play a role in motor development. The trend of food intake in agricultural areas is vegetable consumption, while low animal protein intake will affect the nutritional status and development of toddlers. Objectives: This study aimed to analyze the correlation between nutritional status and motor development in toddlers aged 24-59 months in agricultural areas. Methods: This was a cross-sectional study with a sample size of 65 subjects aged 24-59 months in Sumowono, Semarang Regency, Central Java. The variables studied were nutritional status weight-for-age z-scores (WAZ), weight-for-height z-scores (WHZ), and height-for-age z-scores (HAZ) measured using digital and microtome scales, as well as gross motor and fine motor development measurements with observations and interviews based on the Standard of Child Development Achievement (STPPA) questionnaire. Univariate and bivariate data were then analyzed statistically using the Spearman rank correlation test. Results: Based on anthropometric measurements, 10.8% of toddlers were underweight; 1.5% were overweight; 4.6% were wasting; 9.2% had a possible risk of being overweight; and 40% were stunted. A total of 15.4% of toddlers had severe gross motor delays, and 13.8% had fine motor delays. WAZ (p-value=0.003; r=0.366) and HAZ (p-value<0.001; r=0.633) had relationships with gross motor skills. Both WAZ (p-value=0.019; r=0.291) and HAZ (p-value<0.001; r=0.719) also had relationships with fine motor skills. However, there was no relationship between WHZ with gross motor (p-value=0.935) and fine motor (p-value=0.168). Conclusions: Toddlers with good nutritional status (WAZ and HAZ) will have good gross and fine motor development.